Mitochondria-engine with self-regulation to restore degenerated intervertebral disc cells via bioenergetic robust hydrogel design - Wang, Juehan; Jiang, Yulin; Zhu, Ce; Liu, Zheng; Qi, Lin; Ding, Hong; Wang, Jing; Huang, Yong; Li, Yubao; Song, Yueming; Feng, Ganjun; Zhang, Li; et al. (Bioactive materials, 2024)
Previous studies have confirmed that intervertebral disc degeneration (IDD) is closely associated with inflammation-induced reactive oxygen species (ROS) and resultant cell mitochondrial membrane potential (MMP) decline. Clearance of ROS in an inflammatory environment is essential for breaking the vicious cycle of MMP decline. Additionally, re-energizing the mitochondria damaged in the inflammatory milieu to restore their function, is equally important. Herein, we proposed an interesting concept of mitochondrion-engine equipped with coolant, which enables first to “cool-down” the inflammatory environment, next to restore the MMP, finally to allow cells to regain normal energy metabolism through materials design. As such, we developed a multi-functional composite composed of a reactive oxygen species (ROS)-responsive sodium alginate/gelatin hydrogel infused into a rigid 3D-printed thermoplastic polyurethane (TPU) scaffold. The TPU scaffold was coated with conductive polypyrrole (PPy) to electrophoretically deposit l-arginine, which could upregulate the Mammalian target of rapamycin (mTOR) pathway, thus increasing MMP and energy metabolism to stimulate extracellular matrix synthesis for IVD repair. While the ROS-responsive hydrogel acting as the “mito-engine coolant” could scavenge the excessive ROS to create a favorable environment for IVD cells recovery. Demonstrated by in vitro and in vivo evaluations, the mito-engine system markedly promoted the proliferation and collagen synthesis of nucleus pulposus cells while enhancing the mitochondrial respiration and MMP under oxidative stress. Radiological and histological assessments in vivo revealed the efficacy of this system in IVD repair. This unique bioinspired design integrated biomaterial science with mitochondrial biology, presents a promising paradigm for IDD treatment. [Display omitted] •Hybrid Mito-Engine: Novel hydrogel with 3D-printed scaffold and ROS-responsive gel.•Energy Metabolism Boost: Enhanced mitochondrial potential for disc repair.•ROS Scavenging: Hydrogel effectively scavenges excessive ROS, aiding cell recovery.•Mechanical Biomimicry: Rigid scaffold and soft hydrogel mimic disc mechanics.•In Vivo Efficacy: Proven system efficacy in nucleus pulposus proliferation.